Improved crystallisation of polysilazane‐derived Si3N4/SiC nanocomposites with Fe2O3 catalyst. (20th April 2021) - Zhang, Wenshu; Wang, Shuo; Ding, Honghui; Zhai, Xueying; Yang, De'an
Abstract: In the present study, the use of a 3 wt% Fe2 O3 catalyst improved the crystallisation of polysilazane PSN2. Crystallisation peaks of higher intensity were observed for Si3 N4 and SiC at 1250 °C by using a 3 wt% Fe2 O3 catalyst than at 1500 °C without Fe2 O3 . Besides, the effects of temperature on the morphology of the samples were determined through scanning electron microscopy. Porous structures were observed at 1250 °C and these structures were transformed to flaky and near‐spherical nanoparticles as the temperatures were increased to 1350 and 1450 °C, respectively. Finally, the mechanism of Fe origination from Fe2 O3 reduction, the production of a supersaturated liquid alloy, and the release and diffusion of N2 were proposed for Si3 N4 formation.